Christ–Siemens–Touraine syndrome with palmoplantar keratoderma: A rare association - Sunil K Kothiwala; Mahesh Prajapat; C M Kuldeep (Indian Dermatology Online Journal, 2016)
Christ–Siemens–Touraine syndrome is a form of anhidrotic ectodermal dysplasia (ED) characterized by triad of hypodontia, hypotrichosis, and hypohidrosis. Palmoplantar keratoderma is a characteristic feature of hidrotic forms of ED. Till date, only two cases have been reported of Christ–Siemens–Touraine syndrome with palmoplantar keratoderma; here we report a similar case emphasizing this rare association.